A novel accessory gene product of tick-borne Dhori-Orthomyxovirus, encoded by overlooked spliced transcripts of RNA segment 6 - Bendl, Elias; Lampo, G.; Chlanda, Petr; Schnettler, E.; Kochs, G.; Dengjel, J.; Graf, L. (Journal of virology, 2025)
Dhori virus (DHOV) (Orthomyxoviridae, genus: Thogotovirus) is a tick-borne virus with a segmented, negative-sense RNA genome. Thogotoviruses can be divided into two clades, Thogoto-like and Dhori-like viruses, which differ in their coding strategy of the segment 6 encoded matrix protein (M): Thogoto viruses translate M from spliced transcripts and a long M (ML) from unspliced transcripts. Dhori-like viruses encode their M using unspliced transcripts, whereas no splicing or additional coding capacity has been described, yet. Here, we identified spliced transcripts of segment 6 in DHOV-infected cells by RT-PCR and sequencing. The gene product M2-248 codes for a truncated, 186 amino acids-long N-terminal moiety of M fused to 62 C-terminal amino acids from a -1 shifted reading frame. The splicing sites and the amino acid sequences of the C-terminal M2 part are conserved in Dhori-like viruses. Expression of M2-248 was confirmed in infected cells by mass spectrometry and western blot analysis and was detected in purified virions. Recombinant DHOV(Delta M2) lacking M2-248 showed reduced virulence compared with recombinant wild-type in mice but no attenuation in cell culture and no effect on virion assembly and morphology. An interferon antagonistic function of M2-248, similar to THOV ML, was excluded. Thus, our data suggest that DHOV segment 6 splicing and expression of M2-248 protein affect virulence in mammals by a mechanism distinct from THOV-ML. It remains to be analyzed how M2-248 might affect viral host switch and replication in ticks.IMPORTANCEDhori and Thogoto viruses are tick-transmitted orthomyxoviruses comprising two clades differing in the coding strategy of their matrix protein. The recent detection of Dhori-like Bourbon virus (BRBV) highlighted their zoonotic potential. M of Dhori-like viruses is translated from a collinear transcript of the smallest of the six genomic ssRNA segments. Thogoto-like viruses express M from spliced transcripts, and unspliced transcripts encode an extended ML protein. No analogous splicing event or additional gene product has been characterized for Dhori-like viruses, yet. Here, we describe the hitherto overlooked splicing of segment 6 transcripts of Dhori virus. The 5'-part of the processed transcript is collinear with the M-ORF, whereas splicing shifts it into a -1 frame. The predicted product M2-248 was detected in infected cells. Recombinant Dhori virus lacking M2 was attenuated in vivo, whereas replication in mammalian cells was not impaired, suggesting a modulatory function of M2 in in vivo-specific, cellular immunity-related processes.
Veröffentlicht: 15 September 2025
Gesehen am 30.01.2026